Application of Fault Fracture Density in Determination of Zones with High Permeability Levels on Geothermal Surface Manifestations in the Sukarame Region, Sukabumi Regency, West Java Province - Ramadhan, Galih Hadisurya; Haryanto, Agus Didit; Haryanto, Iyan; Hadi, Mochamad Nur; Mustofa, Santia Ardi (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
Indonesia is a country with quite large geothermal potential with a volcanic distribution that extends from Sabang to Merauke. The total potential for developing geothermal energy in Indonesia can reach 28,579 MWE if it is developed properly. This study was conducted for determining a permeable zone at the research location which is in Sukarame Village that can be related to the emergence of hot springs as a geothermal surface manifestations, besides that this research can also provide an overview of the general direction of geological structures that may develop in the research area. The method used in this study is Fault fracture density analysis which can determine the zone with a high level of permeability based on the lineament pattern drawn from remote sensing interpretation. The main data source for interpreting lineament pattern analysis is DEMNAS imagery which built from 3 satellites imagery including IFSAR, TERRASAR-X and ALOS PALSAR. The lineament pattern that have been analyzed then processed computationally into rose a diagram to get the general direction of structural geology which may develop. The total length of the lineament pattern is also calculated to obtain the lineament density value that leads to the determination of the permeable zone. The lineament pattern in the research area has a general direction of northeast-southwest, while the lineament density value in the study area has a value range of 4534.714078 – 9084.119758 m/km2. Areas with a high level of permeability coincide with the point of hot springs as a manifestation of the geothermal surface.